Tissue-specific T cell profiles in Mycobacterium tuberculosis uninfected IGRA negative and positive individuals - Ahimbisibwe, Gift; Nakibuule, Marjorie; Ssejjoba, Marvin Martin; Bisoboka, Claire Precious; Akello, Feddy Gift; Turyasingura, Marvin Joven; Mulwana, Rose; Nabulime, Josephine; Babirye, Febronius; Kizito, Musana Abdusalaamu; Lekuya, Hervé Monka; Adakun, Akello Suzan; et al. (Frontiers in Tuberculosis, 2025)
IntroductionInterferon-gamma release assays (IGRAs), such as the T-SPOT.TB and QuantiFERON-TB Gold, are commonly used to detect immune responses to Mycobacterium tuberculosis (M.tb) and identify latent TB infection. However, their role in reflecting immune dynamics within tissues, especially in the absence of active disease, remains unclear.MethodsPost-mortem tissues, including lung, lymph nodes, spleen, and bronchoalveolar lavage, were collected from apparently healthy, HIV-negative road traffic accident victims. M.tb infection was ruled out using liquid MGIT culture, while M.tb exposure history was assessed with the TSPOT.TB assay. T and B cell phenotyping was performed using a 29-color flow cytometry panel, with data analyzed in FlowJo and GraphPad Prism.ResultsOf the 52 individuals recruited, 48% were IGRA-positive (TSPOT+). Using a 29-color flow cytometry panel, we analyzed T and B cell populations across various tissues. We observed similar overall frequencies of CD3, CD4, CD8, and CD19 cells, as well as memory T and B cell subsets defined by CCR7/CD45RA and IgD/CD27 between TSPOT+ and TSPOT individuals. Notably, in the lungs, TSPOT+ individuals exhibited a higher frequency of CD4+ tissue-resident memory (TRM) T cells, along with increased expression of KLRG1, a marker of terminal differentiation, on mature CD4+CD27 T cells. This phenotype was specific to CD4 T cells in the lungs, highlighting the known role of CD4 T cells in TB immunity and their localization to the primary site of infection.DiscussionOur findings suggest that IGRA positivity, while indicating immune memory, may also be associated with highly differentiated CD4 T cells in tissue-specific compartments, particularly in the lungs. These localized immune changes raise important questions about the long-term effects of chronic immune engagement following repeated M.tb exposure in endemic settings. Further research is needed to assess the clinical implications of these findings, including their impact on susceptibility to future infections or disease progression.